Um mundo ao alcance de crianças e jovens: notas sobre o protagonismo de crianças e jovens em orçamento público em cidades brasileiras - Streck, Danilo R. (Cadernos de Educação, 1970)
Este artigo reúne elementos para compreender a participação de crianças e de jovens na administração pública, em especial no orçamento. Detém-se primeiramente na análise das motivações para integrar jovens e crianças em assuntos até há pouco considerados como exclusividade de um reduzido grupo de técnicos e políticos adultos. Apresenta e analisa fatos e dados de algumas experiências, com ênfase no OP-Criança na cidade de São Paulo. Destaca, na conclusão, que o fato de manter crianças e jovens num mundo separado, ainda que sob o argumento da proteção, além de tolher o desenvolvimento como indivíduos e como cidadãos, representa o desperdício de um potencial de criatividade e de energia das quais as atuais sociedades necessitam para se repensar e refazer. Palavras-chave: protagonismo, crianças, jovens, orçamento participativoA world within reach of children and youngsters: notes of children and youngsters as protagonists in public budget matters in Brazilian citiesAbstractThis paper presents elements to understand the participation of children and youngsters in the public administration, mainly regarding the public budget. Firstly, I have analyzed the motivation that leads to the integration of youngsters and children in matters which were considered a privilege of a limited group of adult technicians and politicians in the past. I have also presented and analyzed facts and data collected in some experiences, specially the Public Budget for Children in São Paulo, SP. As a conclusion, I argue that the fact of keeping children and youngsters apart from the world, even if the justification for doing so is their protection, not only prevents them from developing as individuals and citizens, but also represents the waste of potential creativity and energy which today's societies need in order to rethink and rebuild themselves.Key words: Protagonism, Children, Youngsters, Public Budget.